Communal Tenure and Rural Poverty : reflections on land transactions in Svosve Communal Area, Zimbabwe /: reflections on land transactions in Svosve Communal Area, Zimbabwe. (April 2008) - Chimhowu, Admos; Woodhouse, Philip
No abstract available